Professora alfabetizadora e crianças em processo de (cri)ação literária : voos em (trans)formação - Carlos, Thaís Rodrigues (2021)
This master's dissertation is linked to the Group of Studies and Research Oral Language, Reading and Writing in Childhood (GEPLOLEI), of the Graduate Program in Education at the Federal University of Mato Grosso - Campus Cuiabá (PPGE-UFMT) and to the line of research “School Cultures and Languages”. The objective is to understand literary reading and writing practices through the discursive perspective of literacy and Historical-Cultural Theory. Language is considered as a discursive assumption by Smolka (1993, 2012), the theoretical perspective of the philosopher Bakhtin (2011) who discusses dialogism and Vygotsky's (2007) statements and postulates about thought, language and child development. As it is a qualitative research, participant observation (BECKER, 1993) and collaborative research between researcher, children and children children are used (IBIAPINA, 2016; BANDEIRA, 2016; HORIKAWA, 2008). The production of data took place through the theoretical review of texts on the subject, the analysis of children's and literacy narratives, audiovisual records of episodes of pedagogical activities, transcription and documentary material. This study seeks to answer: What are the teaching practices of literary reading and literary writing in an online classroom of the literacy cycle that contribute to literacy; how the Historical Cultural Theory and the discursive perspective contribute to the production of meanings of children and the teacher / researcher during interactions in an online classroom and which theoretical and methodological aspects enable the process of (re) elaboration, imagination and childhood upbringing. n this way, the reading and literary writing of a class in the literacy cycle that followed from 2019 to 2021 and the teacher constitution of a beginner literacy teacher were analyzed as categories of analysis. It was found the importance that the activities in the remote classes work the production of meanings through art and literature, allowing the children-students and teacher to appropriate the senses of reading and writing. Also that children's literature and literary books produced by children show that they produce culture and art, as well as (re) create and create forms of expression that are fundamental to the processes of discursive literacy. Children's literature and art were also found to be fundamental for the development and for the aesthetic and ethical constitution of children-students and teachers, as flight processes take place through the right and access to these important cultural instruments. We think that literary reading and working with aesthetic education allows imagination and (re) creation to gain wings for children to explore (un) known paths, we also argue that children's literature of aesthetic quality enables teaching processes -learning contributes to the development of all human potential.